Time performance analysis of advanced encryption standard and data encryption standard in data security transaction - Zolidah Kasiran; Hikma Farah Ali; Noorhayati Mohamed Noor (Institute of Advanced Engineering and Science, 2019)
The advancement of the data communication technologies has increased the traffic of data exchange over the internet and at the same time created the opportunity of data attack by various party. This paper present Time Performance Analysis Of Advanced Encryption Standard And Data Encryption Standard in Data Security Transaction. In this study we proposed an AES algorithm with different key size, and different file format. Our aim is to safely to transfer the file for using the AES algorithm. Proposed algorithm has done by analyzing the different time taken for both AES and DES, experiments were done by three different file format which were text, image, and voice. Each file format type was tested with five different file sizes. The result of each experiments were analysed and it was confirmed that the AES algorithm have better performance in term of time taken as compared to DES.